Expressão de Pentraxina 3 no líquido amniótico e imunolocalização nas membranas corioamníóticas de gestações de termo e complicadas por parto pré-termo - Martin, Laura Fernandes [UNESP] (2013)
Changes in the Pentraxin 3 (PTX3) expression throughout pregnancy are not well established but in pregnancy complications higher expression have been described. To evaluate expression of PTX3 in amniotic fluid (AF) throughout the last weeks of normal pregnancies and in pregnancies complicated by preterm delivery (PTD). A crosssectional study was conducted with 120 pregnant women in term and PTD. Samples of AF from all patients were obtained during cesarean section. Amniochorion membranes were collected to localization of PTX3 using immunohistochemistry. Regarding term pregnancies, PTX3 expression increased slightly throughout weeks, but these expressions are not statistically different. Among preterm pregnancies, those with preterm labor (PL) had a higher PTX3 levels than those not in labor and there was a risk increased of 1% in the occurrence of PL when there was a rise of 1 pg/mL of PTX3. Amniotic epithelial, chorionic and decidual cells presented immunoexpression of PTX3. PTX3 is a physiologic constituent of the AF, and its expression is elevated in the presence of spontaneous PL suggesting that PTX3 play a role in the innate immune response during the gestational complications that are related with an infectious/inflammatory conditions. The amniochorion membranes are sources of PTX3